Basic principles and requirements of self compacting concrete / Mohd Syahrul Hisyam Mohd Sani and Ahmad Rasidi Osman - Mohd Sani, Mohd Syahrul Hisyam; Osman, Ahmad Rasidi (Universiti Teknologi MARA Cawangan Pahang, 2005)
Self compacting concrete (See), also referred to as self consolidating concrete, is able to flow and consolidate under its own weight. It is cohesive enough to fill the spaces of almost any size and shape without segregation or bleeding. A see, which has excellent deformability and resistance to segregation and can be filled in heavily, reinforced formwork without vibrators. The physical behaviour of the wet concrete extremely flow-able cohesive means that it can be placed without the need for vibration, yet giving a hardened concrete which exhibits excellent results for surface finish, density and strength. The required workability for casting depends on several factors, such as the type of construction, the selected placement and consolidation methods, the shape of formwork, and the congestion nature of the reinforcement. With the increasing use of congested reinforcements in mat foundations and moment resisting reinforced concrete structures, there is a growing interest in specifying highly flow-able concrete (Okamura, Ozawa, Ouchi 2000). New see technology can eliminate the need for vibration, making it possible to reduce labour costs while improving the overall work environment for construction personnel. Faster placement and less finishing time can improve productivity and profitability. Increased flow-ability and consolidation can improve appearance and enhance the durability of the finished element.